Upregulation of Nox4 induces a pro-survival Nrf2 response in cancer-associated fibroblasts that promotes tumorigenesis and metastasis, in part via Birc5 induction - Shakeel Mir; Briana D. Ormsbee Golden; Brandon J. Griess; Raghupathy Vengoji; Eric Tom; Elizabeth A. Kosmacek; Rebecca E. Oberley-Deegan; Geoffrey A. Talmon; Vimla Band; Melissa LT. Teoh-Fitzgerald (Breast Cancer Research, 2022)
Abstract Background A pro-oxidant enzyme, NADPH oxidase 4 (Nox4) has been reported to be a critical downstream effector of TGFβ-induced myofibroblast transformation during fibrosis. While there are a small number of studies suggesting an oncogenic role of Nox4 derived from activated fibroblasts, direct evidence linking this pro-oxidant to the tumor-supporting CAF phenotype and the mechanisms involved are lacking, particularly in breast cancer. Methods We targeted Nox4 in breast patient-derived CAFs via siRNA-mediated knockdown or administration of a pharmaceutical inhibitor (GKT137831). We also determine primary tumor growth and metastasis of implanted tumor cells using a stable Nox4-/- syngeneic mouse model. Autophagic flux of CAFs was assessed using a tandem fluorescent-tagged ptfl-LC3 plasmid via confocal microscopy analysis and determination of the expression level of autophagy markers (beclin-1 and LC3B). Nox4 overexpressing CAFs depend on the Nrf2 (nuclear factor-erythroid factor 2-related factor 2) pathway for survival. We then determined the dependency of Nox4-overexpressing CAFs on the Nrf2-mediated adaptive stress response pathway for survival. Furthermore, we investigated the involvement of Birc5 on CAF phenotype (viability and collagen contraction activity) as well as the expression level of CAF markers, FAP and αSMA. Conclusions We found that deletion of stroma Nox4 and pharmaceutically targeting its activity with GKT137831 significantly inhibited orthotopic tumor growth and metastasis of implanted E0771 and 4T1 murine mammary carcinoma cell lines in mice. More importantly, we found a significant upregulation of Nox4 expression in CAFs isolated from human breast tumors versus normal mammary fibroblasts (RMFs). Our in situ RNA hybridization analysis for Nox4 transcription on a human breast tumor microarray further support a role of this pro-oxidant in the stroma of breast carcinomas. In addition, we found that Nox4 promotes autophagy in CAFs. Moreover, we found that Nox4 promoted survival of CAFs via activation of Nrf2, a master regulator of oxidative stress response. We have further shown Birc5 is involved as a downstream modulator of Nrf2-mediated pro-survival phenotype. Together these studies indicate a role of redox signaling via the Nox4-Nrf2 pathway in tumorigenesis and metastasis of breast cancer cells by promoting autophagy and survival of CAFs.